An evaluation of the functions of the assistant probation officer as a new occupational category in probation practice - Carloo, Ruwayda (2002)
Includes bibliography.The main aim of this study is to evaluate the functions of the assistant probation officer as a new occupational category in probation practice. The study also explores the knowledge and insight of the functions of assistant probation officers on the part of related role players, namely, probation officers (including the supervisors of assistant probation officers), magistrates, prosecutors, officials of the South African Police Service and the recipients of the service viz. school principals, teachers, youth, parents as well as community leaders in a deep rural area. The primary respondents comprised of all the assistant probation officers involved in the pilot project as well as their supervisors. The sampling method was used for the related role players and recipients of the service. The researcher used mainly a qualitative approach that included questionnaires and interview schedules. The questionnaires were independently completed by the assistant probation officers and the interview schedules were completed by means of face-to-face interviews with related role-players. Open*ended interviews were held during on-site evaluation visits to projects with the selected sample of recipients of the service. This research can also be regarded as an exploratory study as it explores and evaluates an unknown area in order to gain new insights. The process of triangulation was applied due to the variety of data collection methods. The study found that there was an absolute necessity for the services and the sustainability thereof by assistant probation officers, and of the ultimate incorporation of this occupational category into probation practice. The findings also indicated a lack of knowledge and insight on the part of justice and police officials regarding the functions of assistant probation officers as well as the importance of structured training and the provision of the basic resources for assistant probation officers to function adequately. Therefore a holistic approach to the incorporation of this service into probation practice is required by the Department of Social Development to address the findings of this study